Features of the use of specialized languages for the construction of geometric models of cellular objects in fi element modeling and optimization calculations - V. V. Naprasnikov; Yu. V. Polozkov; A. V. Borodulya; D. P. Kunkevich (Системный анализ и прикладная информатика)
To perform optimization calculations based on the finite element approach in accordance with the criteria accepted by the researcher, it is necessary to first create a parametric geometric model of the product so as to be able to further determine their optimal values by varying the geometric parameters of the project. Since one of the main approaches to the formation of the optimization model is the use of cellular aggregates, the urgent issue is the construction of such geometric objects. The possibility of using the Python language in the SpaceClaim environment to build periodic placeholders is considered. Code fragments and construction results for one of the placeholder types are given. An example of the APDL code for ANSYS of a different type of placeholder is given. The statement of the optimization problem is described and the results of optimization calculations for this placeholder are presented using the example of one construction.